Um olhar para a Economia Circular e a Simbiose Industrial como base para o avanço da Política Nacional de Resíduos Sólidos - Fagliari, Raphael Augusto (Universidade Federal de São Carlos, 2023)
The traditional, linear, and open economic system often neglects the environmental impacts caused by natural resource exploitation and waste generation. In this context, there is a growing need to transition to a circular economic model, where the relationship between the economy and the environment is more harmonious and sustainable. Circular Economy (CE) has gained prominence in several nations as an approach that aims to keep products, their added value, as well as their materials and resources within a continuous production cycle. In Brazil, the Solid Waste National Policy (SWNP) plays a fundamental role as a regulatory framework. It not only emphasizes the importance of recycling but also introduces modern and essential concepts in waste management. Additionally, the SWNP adopts a systemic approach that covers the entire lifecycle with the notion of shared responsibility. This study aims to assess whether the advancement of CE-related practices in Brazil is possible through the country's main legal instrument, which is the SWNP. It also seeks to provide alternatives, including Industrial Symbiosis (IS), to improve Reverse Logistics (RL) practices and overcome obstacles. At the micro level, the SWNP emphasizes eco-design, waste reduction, and shared responsibility, involving waste pickers and consumers. At the meso level, cooperation between the public and private sectors is promoted but lacks clear support mechanisms. At the macro level, the SWNP does not adequately address urban transformation, collaborative consumption, and zero-waste programs. The cultural and historical evolution of waste management in Brazil is highlighted, focusing on the role and importance of waste pickers. From tigers to waste pickers, socially marginalized individuals whose image was linked to social exclusion carried out waste collection and disposal. The credit-based RL model is a trend, but there are also risks in relying on this model. The importance of the protector-receiver principle is emphasized, as well as the need for more specific regulations on incentives to promote RL, as in the presented case study. IS is a promising approach to optimize resource use and reduce waste, which can be leveraged through economic incentives and regulations, along with the involvement of local governments as facilitators. The proposal of Regional Agreements is an initiative to promote symbiotic practices in specific regions, aligning with the SWNP and Regional Agreements. These agreements would include clear goals, performance indicators, and a monitoring and evaluation system. The government would act as a moderator and provide financial and technical support.
A look at the Circular Economy and Industrial Symbiosis as a basis for advancing the National Solid Waste Policy
Keywords: Política Nacional de Resíduos Sólidos; Economia circular; Simbiose Industrial; Logística reversa; Acordo regional; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL